Kartagener syndrome: A case report - Ibrahim, Rahaf (Can J Respir Ther, 2021)
Kartagener syndrome is a rare, autosomal recessive genetic disorder that causes defects in the action of ciliary movement, comprises of triad situs inversus, chronic sinusitis, and bronchiectasis. We present the case of a 3-year-old boy with repeated respiratory infections and pneumonic infections presenting with acute respiratory failure. He was diagnosed with Kartagener syndrome based on his clinical presentation and imaging features. The current diagnosis was consistent with severe acute bronchitis. He was managed initially with conventional medical therapy, but he didn’t respond and was transferred immediately to the pediatric intensive care unit where noninvasive ventilation was administered. He had shown significant predictors of early noninvasive ventilation failure and was mechanically ventilated, after which, he was disconnected from the ventilator and discharged without complications. In patients presenting with recurrent upper and lower respiratory tract infections, Kartagener syndrome should always be kept in mind. The correct diagnosis of this disorder in early life is very important to prevent complications and improve patients’ quality of life.